Analisis Struktur Gedung POP Hotel Terhadap Beban Gempa Dengan Metode Pushover Analysis - Arifin, Zainal; Suyadi, Suyadi; Sebayang, Surya (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
In a fact, the development of Indonesian building codes demand higher design earthquake load.This condition generates the need for retrofitting in existing building that was design with olderbuilding codes, in purpose to acquire the safe building performance. The significant load increaseshown in the latest building code (SNI 1726-2012) gives the urgency to perform seismic riskasessment and retrofit design for this building.Seismic risk of the building is determined from the performance level through static non-linearanalysis (pushover) based on the design earthquake of the new code (SNI 1726-2012). This resultmeans that the damage control performance level, unless retrofitting is performed on each of thedeficient element.Keywords : SNI 1726-2012, pushover, damage control, load of earthquake.